Persistence of symptoms and return to work after hospitalization for COVID-19 - de Azevedo, Helena Moraes Jardim; Dos Santos, Nataly Winni Fernandes; Lafetá, Mariana Lima; de Albuquerque, André Luis Pereira; Tanni, Suzana Erico [UNESP]; Sperandio, Priscila Abreu; Ferreira, Eloara Vieira Machado (My University, 2022)
Many patients hospitalized with COVID-19 were unable to return to work or their return was delayed due to their health condition. The aim of this observational study was to evaluate the impact of moderate-to-severe and critical COVID-19 infection on persistence of symptoms and return to work after hospital discharge. In this study, two thirds of hospitalized patients with pulmonary involvement reported persistence of symptoms six months after COVID-19 infection, such as memory loss (45.5%), myalgia (43.9%), fatigue (39.4%), and dyspnea (25.8%), and 50% slowly returned to work, with repercussions due to fatigue and/or loss of energy.
Keywords: COVID-19/complications; COVID-19/rehabilitation; Hospitalization; Return to work; Survivors